Ion membrane electrolyzer
By designing multiple independent electrolytic cell tank groups and new formula anode coatings, the problems of limited production and short electrode life of traditional electrolytic cells are solved, and the results of improved yield, improved chlorine gas purity and improved current efficiency are achieved.
Patent Information
- Application Number
- CN201910474908.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-06-03
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2039-06-03
AI Technical Summary
Due to the limited size of the tank frame, traditional ion membrane electrolytic cells have limited output, and the short electrode life is short, the high oxygen content affects the purity of chlorine and the current efficiency decreases.
A new ion film electrolytic cell was designed, using multiple independent electrolytic unit cell groups, locked by copper row end plates, freely assembled according to production capacity requirements, sealed and insulated with fluoroplastics, and the anode coating adopts a new formula process to improve the Oxygen evolution potential and electrode life.
It has achieved the advantages of improved production of the electrolytic cell, extended electrode life, improved chlorine gas purity, improved current efficiency, and has the advantages of operating stability and high production efficiency.
Smart Images

Figure CN110219012B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an ion membrane electrolyzer. Background Art
[0002] Ion membrane electrolyzer is a special equipment developed with the application of ion membrane in caustic soda production. Its basic function is to install ion selective exchange membrane between anode and cathode. Refined light brine is introduced into the anode chamber, pure water or low concentration alkali solution is introduced into the cathode chamber, and the electrolytic cell is powered on to produce electrolytic reaction, chlorine is produced in the anode chamber, hydrogen is produced in the cathode chamber, and sodium ions (Na+) pass through the ion membrane from the anode side to the cathode side under the promotion of the electric field, and combine with the hydroxide ions (OH-) of the cathode to produce caustic soda (NaOH). Therefore, since the development of the electrolytic cell, people have carried out research and improvement, mainly focusing on the structure of the electrolytic cell, power supply mode, solution circulation mode, electrode effective area, distance between electrodes, etc. Its main purpose is to meet the production of high-quality products, reduce side reactions, high efficiency and energy saving, safety and environmental protection, etc. Therefore, the development of the chlor-alkali industry is also a process of development from high energy consumption, high pollution, and high emissions to new energy, greening, and new environmental protection.
[0003] The traditional ion membrane electrolyzer is a structure in which multiple electrolytic cell groups are close together and connected and fixed together on a single cell frame. This type of ion membrane electrolyzer is limited by the size of the cell frame, which limits the output of the entire ion membrane electrolyzer. In addition, if an electrolytic cell group fails, the entire machine needs to be stopped and the failed electrolytic cell group needs to be replaced for repair. The disassembly and assembly remain unchanged, which reduces work efficiency.
[0004] On this basis, the anode coating of the traditional electrolytic cell generally adopts titanium-based ruthenium titanium coating. However, after the production practice test, it was found that the titanium-based ruthenium titanium coating has the following defects: the electrode life is short, the oxygen content in the produced chlorine is too high, which affects the purity of the chlorine and causes the current efficiency to decrease. Therefore, it is necessary to increase the oxygen evolution potential of its active coating, reduce the chlorine evolution potential, and increase the electrode life. Summary of the invention
[0005] The object of the present invention is to overcome the above-mentioned shortcomings and provide a new type of ion membrane electrolyzer, which our company named JMH-5 membrane-pole distance ion membrane electrolyzer.
[0006] The object of the present invention is achieved in that:
[0007] An ion membrane electrolyzer comprises a cell frame, on which a plurality of electrolytic cell groups are arranged, and both ends of the plurality of electrolytic cell groups are respectively locked by copper bar end plates, the copper bar end plates are copper bar end plates fixed on a fixed seat or movable copper bar end plates fixed on a top rod seat, and different numbers of electrolytic cell groups and copper bar end plates for locking the plurality of electrolytic cell groups are selected according to production capacity requirements, and the copper bar end plates are connected to a power supply.
[0008] As a preferred embodiment, each electrolytic unit cell group is respectively provided with a liquid inlet and a liquid outlet, the liquid inlet at the lower end of each electrolytic unit cell group is respectively connected to the same liquid inlet distribution pipe through a liquid inlet pipe at a corresponding position, and the liquid outlet at the upper end of each electrolytic unit cell group is respectively connected to the same liquid outlet main pipe through a liquid outlet pipe at a corresponding position.
[0009] As a preferred embodiment, the liquid inlet pipe and the liquid outlet pipe are made of fluoroplastic flexible hoses.
[0010] As a preferred embodiment, the electrolytic unit cell group includes an anode unit, a cathode unit and an ion membrane arranged therebetween, the frame bars of the anode unit and the frame bars of the cathode unit are connected by a screw group, an insulating gasket is arranged between the frame bars of the anode unit and the frame bars of the cathode unit, and sealing strips are arranged between the insulating gasket and the frame bars on both sides.
[0011] Preferably, the anode unit comprises an anode disk, a depression formed by bending the anode disk forms an anode chamber, an anode gas-liquid separation box is arranged at the upper end of the anode chamber, a vertically arranged anode rib plate is arranged in the anode chamber below the anode gas-liquid separation box, a titanium-nickel composite plate is arranged at the position of the anode rib plate on the back side of the anode disk corresponding to the anode rib plate, an anode mesh is arranged on the top surface of the anode rib plate, obliquely arranged circulation plates are arranged between adjacent anode rib plates, and an anode liquid inlet insertion tube is arranged at the lower end of the anode chamber.
[0012] Preferably, the cathode unit includes a cathode disk, a cathode chamber is formed by a depression formed by bending the cathode disk, a cathode gas-liquid separation box is arranged at the upper end of the cathode chamber, a vertically arranged cathode rib plate is arranged in the cathode chamber below the cathode gas-liquid separation box, a cathode bottom net is arranged on the top surface of the cathode rib plate, a cathode elastic net is arranged on the surface of the cathode bottom net, a cathode surface net is arranged on the surface of the cathode elastic net, and a cathode liquid inlet insertion tube is arranged at the lower end of the cathode chamber.
[0013] As a preferred embodiment, a sacrificial electrode for absorbing reverse current is also installed in the cathode chamber.
[0014] As a preference, the anode mesh is a titanium plate expanded mesh, and an active coating is provided on the titanium plate expanded mesh.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] 1. Fluoroplastic is used for sealing and insulation between the cathode and anode, which has the advantages of high temperature resistance, aging resistance and chemical corrosion resistance. The assembled unit slot group will not leak during operation.
[0017] 2. Each unit slot group is independent. If one of them fails, just stop the machine and replace it without affecting other unit slot groups.
[0018] 3. Because it has an independent unit slot group and a simple and reliable electric slot frame and lock slot structure, it is particularly suitable for the new process requirements of automatic start-up and safety protection, emergency chain parking, Industry 4.0 big data collection and automated operation using artificial intelligence AI technology proposed and gradually implemented by modern chlor-alkali technology.
[0019] 4. Because the cell groups are back-to-back conductive, there are requirements for selecting conductive materials and ensuring sufficient contact area. The design of the JHM-5 electrolytic cell takes these requirements into consideration, which can avoid the voltage drop loss caused by the back-to-back contact resistance in similar electrolytic devices abroad.
[0020] Therefore, the ion membrane electrolyzer of the present invention has the advantages of good operation stability, free assembly and deployment according to production capacity requirements, low power loss, high production efficiency and high production capacity.
[0021] In addition, the anode coating using the new formulation process has the following advantages:
[0022] 1. High oxygen evolution potential, strong catalytic ability, high conductivity, and not prone to oxygen evolution side reaction;
[0023] 2. Stable performance, corrosion resistance, long service life, the electrode can be re-coated and continued to be used after failure;
[0024] 3. Electrode cost is effectively controlled;
[0025] 4. To improve product quality, the chlorine gas must be of high purity and low oxygen content (below 0.8%). BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a front view of the general diagram of the ion membrane electrolyzer of the present invention.
[0027] Figure 2 It is a side view of the overall diagram of the ion membrane electrolyzer of the present invention.
[0028] Figure 3 It is a side view of the electrolysis unit cell group.
[0029] Figure 4 for Figure 3 A partial enlarged view of point A.
[0030] Figure 5 This is the front view of the anode unit.
[0031] Figure 6 Rear view of the anode unit.
[0032] Figure 7 for Figure 5 BB section view in.
[0033] Figure 8 This is the front view of the cathode unit.
[0034] Fig. 9 This is the rear view of the cathode unit.
[0035] Fig.10 for Figure 8 CC cross-sectional view.
[0036] in:
[0037] Fixed seat 1
[0038] Ejector seat 2
[0039] Fixed copper bar end plate 3
[0040] Ejector group 4
[0041] Mobile copper bar end plate 5
[0042] Intermediate connecting copper bar 6
[0043] Mobile connection copper bar 7
[0044] Electrolysis unit cell group 8, anode unit 801, anode disk 801., anode gas-liquid separation box 801.2, anode rib plate 801.3, anode net 801.4, circulation plate 801.5, anode liquid inlet insertion tube 801.6, titanium-nickel composite plate 801.7, cathode unit 802, cathode disk 802.1, cathode gas-liquid separation box 802.2, cathode rib plate 802.3, cathode bottom net 802.4, cathode elastic net 802.5, cathode surface net 802.6, cathode liquid inlet insertion tube 802.7, ion membrane 803, screw group 804, insulating gasket 805, sealing strip 806
[0045] Liquid inlet pipe 9
[0046] Liquid distribution pipe 10
[0047] Liquid outlet pipe 11
[0048] Liquid outlet main pipe 12. DETAILED DESCRIPTION
[0049] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] See also Figure 1-10 The present invention relates to an ion membrane electrolyzer, which comprises a fixed seat 1 and a push rod seat 2 located on both sides of the fixed seat 1, wherein fixed copper bar end plates 3 are installed on the left and right sides of the fixed seat 1 through an insulating plate, and the two fixed copper bar end plates 3 are connected by a detachable intermediate connecting copper bar 6, and a push rod group 4 is arranged on one side of the fixed seat 1 of the two push rod seats 2, and a movable copper bar end plate 5 is arranged at the free end of the push rod group 4, and a movable connecting copper bar 7 is led out from the movable copper bar end plate 5, and a plurality of electrolytic unit cell groups 8 are arranged between the movable copper bar end plate 5 and the fixed copper bar end plate 3, and the push rod group 4 is tightened to make the plurality of electrolytic unit cell groups 8 fit tightly, and the plurality of electrolytic unit cell groups 8 fit tightly with the movable copper bar end plate 5 and the fixed copper bar end plate 3 respectively. The front and rear ends of the electrolytic unit cell groups 8 are limited by the side rods on the cell frame.
[0051] Each electrolytic unit cell group 8 is respectively provided with a liquid inlet and a liquid outlet. The liquid inlet at the lower end of each electrolytic unit cell group 8 is connected to the same liquid inlet distribution pipe 10 through a liquid inlet pipe 9 at a corresponding position. The liquid inlet distribution pipe 10 is used to input refined brine and low-concentration alkali solution. The liquid outlet at the upper end of each electrolytic unit cell group 8 is respectively connected to the same liquid outlet main pipe 12 through a liquid outlet pipe 11 at a corresponding position. The liquid outlet main pipe 12 is used to output the output. The liquid inlet pipe 9 and the liquid outlet pipe 11 are preferably made of fluoroplastic flexible hoses.
[0052] The electrolytic cell group 8 includes an anode unit 801, a cathode unit 802, and an ion membrane 803 disposed therebetween. The frame bars of the anode unit 801 and the frame bars of the cathode unit 802 are connected by a screw group 804. An insulating gasket 805 is disposed between the frame bars of the anode unit 801 and the frame bars of the cathode unit 802. A sealing strip 806 is disposed between the insulating gasket 805 and the frame bars on both sides.
[0053] The anode unit 801 includes an anode disk 801.1, and the concave part formed by the bending of the anode disk 801.1 forms an anode chamber. The upper end of the anode chamber is provided with an anode gas-liquid separation box 801.2. Since the bubbles of chlorine produced by electrolysis are relatively large and sticky, they must be crushed, filtered and separated. The setting of the anode gas-liquid separation box has a great effect on the treatment of chlorine and the smooth discharge of liquid, and at the same time avoids the phenomenon of surging liquid discharge causing vibration and wear of the ion membrane. The liquid outlet is set at the upper end, which not only makes the liquid discharge smooth, but also avoids the situation that the liquid inlet pipe does not reach the bottom and the regional electrolyte flow is poor due to the built-in liquid outlet pipe of similar foreign products. A vertically arranged anode rib plate 801.3 is provided in the anode chamber below the anode gas-liquid separation box 801.2, and a titanium-nickel composite plate 801.7 is provided at the position of the anode rib plate 801.3 on the back of the anode disk 801.1, so that the back-to-back contact between two adjacent electrolytic unit cell groups 8 is nickel-nickel contact, rather than direct contact between titanium and nickel with high resistance. An anode mesh 801.4 is provided on the top surface of the anode rib plate 801.3. The anode mesh uses a titanium plate expansion mesh (diamond hole flat mesh) to make an active coating, which has the performance of low chlorine evolution potential and high oxygen evolution potential, and has the functions of protecting ion membrane, low power consumption and low oxygen evolution, ensuring the purity of chlorine. An obliquely arranged circulation plate 801.5 is provided between adjacent anode rib plates 801.3. When the electrolytic cell is in operation, liquid enters the lower part and gas and liquid go out of the upper part, forming a circulation cycle along the circulation plate to ensure the uniformity of medium concentration and temperature in the anode chamber. The lower end of the anode chamber is provided with an anode liquid inlet insertion tube 801.6 made of fluoroplastic material. The anode liquid inlet insertion tube 801.6 is an inserted fluoroplastic liquid inlet distribution tube, which forms a uniform diversion in the anode chamber, has the smallest leakage current, and will not cause the overflow hole to be blocked due to scale accumulation, and the liquid inlet diversion is fully covered. A plurality of holes are evenly distributed on the anode rib plate 801.3. A 2.83m2 electrolytic cell requires at least 26 or more anode rib plates 801.3. A sufficient number of anode rib plates 801.3 can ensure the rigidity and sufficient conductive area of the anode unit 801. The holes on the anode rib plate 801.3 can not only eliminate welding stress, but also enable the medium in the anode chamber to circulate mutually, thereby improving the uniformity of medium concentration and temperature. The flange sealing surface of the anode disk 801.1 is made of titanium-palladium alloy to prevent the occurrence of gap corrosion.
[0054] The cathode unit 802 adopts a structure similar to that of the anode unit 801. The cathode unit 802 includes a cathode disk 802.1. The cathode disk 802.1 is bent to form a cathode chamber. A cathode gas-liquid separation box 802.2 is provided at the upper end of the cathode chamber. A vertically arranged cathode rib plate 802.3 is provided in the cathode chamber below the cathode gas-liquid separation box 802.2. A cathode bottom net 802.4 is provided on the top surface of the cathode rib plate 802.3. A cathode elastic net 802.5 is provided on the surface of the cathode bottom net 802.4. A cathode surface net 802.6 is provided on the surface of the cathode elastic net 802.5. A cathode liquid inlet insertion tube 802.7 made of fluoroplastic material is provided at the lower end of the cathode chamber. A sacrificial electrode (not shown in the figure) for absorbing reverse current is also installed in the cathode chamber. The sacrificial electrode can effectively deal with the damage of the reverse current to the active coating of the cathode during emergency parking. The cathode adopts a membrane pole distance structure (bottom mesh + elastic mesh + surface mesh), and the cathode surface mesh 802.6 adopts advanced precious metal active coating, especially adding platinum, palladium and other components with superior performance and long life, so that the power consumption performance and operation stability of the JHM-5 electrolytic cell reach the international cutting-edge level.
[0055] The above-mentioned characteristics of an ion-exchange membrane electrolyzer are:
[0056] 1. The cell frame is assembled by welding and processing steel sections. It has a simple structure and low manufacturing cost. It can meet the needs of different electrolytic cell areas, quantities and production capacities. It can be made into an electrolytic cell with an annual production capacity of 30,000 tons / unit to 40,000 tons / unit of caustic soda, or an electrolytic cell with an annual production capacity of 5,000 tons / unit. The cell frame can be made into the form of one fixed seat plus two top rod seats as mentioned above, or it can be made into one fixed seat plus a fixed seat with a top rod; the number of top rods is determined according to the size of the electrolytic cell area; in addition to chlor-alkali production, it can also be used to treat salt-containing wastewater in coal chemical industry, pesticide and other industries through electrolysis.
[0057] 2. The JHM-5 electrolytic cell group is an independent cell group consisting of an anode unit, an ion membrane, and a cathode unit. There are sealing strips for sealing and modified PTFE insulating gaskets for insulation between the anode and cathode units. It is assembled through 8 segmented frame strips and several screw groups.
[0058] 3. Several groups of unit cells are suspended on the side bars of the cell rack and insulated from the side bars. End plates with conductive copper bars are configured at both ends. The end plates and the fixed seats of the cell rack are separated by insulating plates. The end plates are pressed against the top rods installed on one side of the fixed seat (the number and specifications of the top rods are determined according to the size of the cell area) to control the distance between the cell groups and can be fine-tuned with temperature and pressure. The copper bars on the end plates are in contact with the electrolytic cells, and the cell groups are in back-to-back contact, so that the current is input from one end and output from the other end to complete the electrolytic production task.
[0059] The anode mesh adopts a titanium plate expanded mesh (diamond hole flat mesh) to make an active coating, and the active coating adopts a brand-new anode coating for ion membrane electrolyzer. The formula of the anode coating for ion membrane electrolyzer is preferably a combination formula of ruthenium, iridium, platinum and titanium, wherein the ruthenium content (Ru35-45mol%), the iridium content (Ir5-15mol%), the platinum content (Pt5-10mol%), and the titanium content (Ti35-45mol%), and 4% molar percentage weight of other additives can be added. The other additives are zirconium chloride or palladium chloride, and a suitable ratio is selected to form a stable rutile structure.
[0060] The above formula is preferably a ruthenium content (Ru 37-43 mol%), an iridium content (Ir 9-15 mol%), a platinum content (Pt 6-9 mol%), a titanium content (Ti 35-40 mol%), and other additives 3-4 mol%.
[0061] Specifically, the carrier of ruthenium is ruthenium trichloride, the carrier of iridium is iridium tetrachloride or chloroiridic acid, the carrier of platinum is chloroplatinic acid or platinum chloride, and the carrier of titanium is titanium tetrachloride.
[0062] The method for making the above-mentioned anode coating for ion membrane electrolyzer for active anode is as follows:
[0063] 1. Make anode titanium mesh (pretreatment of titanium mesh substrate);
[0064] Use TA1 titanium plate expanded mesh as the substrate mesh of the electrode; the titanium plate thickness is 1-1.2mm, the titanium mesh thickness is 1-1.2mm, the mesh has diamond holes, and the mesh pitch is 3*6mm, 3.5*6mm, 4.5*8mm or 5*10mm, etc., preferably the thickness is 1mm and the pitch is 3*6mm;
[0065] The substrate mesh must go through processes such as shearing, degreasing, high-temperature annealing and leveling, sandblasting, pickling, and cleaning to provide a flat, clean, and rough-surfaced substrate to ensure maximum bonding strength and specific surface area of the coating;
[0066] The specific process is as follows:
[0067] 1. Titanium mesh shearing;
[0068] 2. Degreasing treatment (use industrial cleaning agent, soak to remove oil, then clean and dry);
[0069] 3. Clamp the titanium mesh (60-100 sheets as a batch) with a jig and put it into a heat treatment furnace for heat treatment. The jig includes a rectangular upper fixing plate and a lower fixing plate. 60-100 titanium meshes are stacked between the upper fixing plate and the lower fixing plate. Then tighten the tie rods at the four corners of the upper fixing plate and the lower fixing plate to clamp the jig and the titanium mesh. Heat the titanium mesh to 450℃-530℃ in the heat treatment furnace and then cool it down and take it out of the furnace.
[0070] 4. The automatic conveyor sandblasting machine sandblasts the front and back sides of the titanium mesh into a rough surface;
[0071] 5. Use 20-25%Wt sulfuric acid aqueous solution at a temperature of 80℃-85℃ to pickle the titanium mesh;
[0072] 6. Clean the titanium mesh with pure water;
[0073] 7. Drying.
[0074] 2. Making a coating solution for the anode coating;
[0075] A chloride aqueous solution for anode coating of an ion-exchange membrane electrolyzer is prepared according to a formula to form a coating solution;
[0076] Raw materials used: a. ruthenium trichloride (aqueous solution of ruthenium trichloride in hydrochloric acid containing 80-120 g / L of ruthenium or solid ruthenium trichloride with a content of 37%); b. titanium tetrachloride, a chemically pure standard reagent; c. iridium tetrachloride (aqueous solution of iridium tetrachloride in hydrochloric acid containing 80-120 g / L of iridium) or chloroiridic acid; d. chloroplatinic acid or platinum chloride; e. other additives such as zirconium chloride, palladium chloride, etc., with a weight percentage less than 4% by mole (raw material e may or may not be added); f. a solvent selected from aqueous hydrochloric acid, ethylene glycol-butyl ether or n-butanol;
[0077] 3. Making Anode Coating
[0078] The coating liquid is evenly coated on the titanium mesh substrate by multiple coatings. After each coating, it is dried first and then sintered at high temperature. This process is repeated multiple times (8-12 times) and then sintered to form stable precious metal oxide crystals on the surface of the titanium mesh substrate.
[0079] The pre-treated titanium mesh substrate is subjected to multiple automatic electrostatic spraying, drying, and high-temperature sintering in an oxidation furnace according to the coating amount requirements. After the last sintering, the total spray weight increase on the titanium mesh substrate is 25-35g / m 2 , and finally the firing operation and inspection are carried out. The drying temperature is 80-90℃, the high temperature sintering temperature in the oxidation furnace is 400-500℃, the high temperature sintering time in the oxidation furnace is 0.5-1h, and the final firing temperature is 480-530℃. The firing operation is carried out by slowly heating and slowly cooling, and the firing time is 8-12h.
[0080] The specific process is as follows:
[0081] Depending on the total weight increase after sintering, 8-12 cycles of spraying, drying and sintering can be carried out, with each spraying volume of 40-60ml / m 2 , weigh after each sintering, the weight increases by 2-4g / m 2 ,
[0082] Embodiment 1:
[0083] Titanium mesh substrate: mesh pitch 3*6mm, thickness 1mm;
[0084] Anode coating coating liquid: ruthenium trichloride, iridium tetrachloride, chloroplatinic acid, titanium tetrachloride and hydrochloric acid aqueous solution, with the formula raw materials composed of atomic percentage of Ru43:Ir9:Pt8:Ti40;
[0085] The final mass ratio of each raw material used is calculated as follows:
[0086] Ruthenium trichloride: iridium tetrachloride: chloroplatinic acid: titanium tetrachloride = 88.3:15.7:16.8:158.7.
[0087] Production of anode coating: 10 cycles of spraying, drying and sintering, with each spraying volume of 55-60ml / m 2 , weigh after each sintering, the weight increases by 3.5-4g / m 2 After the last sintering, the total weight added by spraying on the titanium mesh substrate is 35-40g / m 2 .
[0088] Product testing indicators:
[0089] 1. Chlorine evolution potential test results: 1.09V-1.10V (indicators: current density 4KA / ㎡, saturated brine, temperature 90℃±1℃, ≤1.13VVS SCE);
[0090] 2. Strengthened weight loss test results: <4mg (index: 30% WtNaoH solution (CP grade), test piece 10C㎡, temperature 90℃±1℃, current density 20KA / ㎡, electrolysis 4 hours, weight loss <6.3mg);
[0091] 3. Tests in a small experimental electrolytic cell device showed that the electrolysis voltage was lower than that of the anode currently used; the purity of chlorine was greater than 98.8% (without acid addition process), and the oxygen content was less than 0.6%.
[0092] From the perspective of product testing indicators, all three test indicators achieved good results.
[0093] Embodiment 2:
[0094] Titanium mesh substrate: mesh pitch 3.5*6mm, thickness 1mm;
[0095] The coating liquid of the anode coating: solid ruthenium trichloride, titanium tetrachloride, iridium tetrachloride, zirconium chloride, platinum chloride and ethylene glycol-butyl ether, the formula is composed of the atomic percentage of Ru37:Ir15:Pt6:Ti39:Zr3:,
[0096] The final mass ratio of each raw material used is calculated as follows:
[0097] Ruthenium trichloride:iridium tetrachloride:chloroplatinic acid:titanium tetrachloride:zirconium chloride=76.0:26.1:12.6:154.8:7.7.
[0098] Production of anode coating: 10 cycles of spraying, drying and sintering, with each spraying volume of 45-50ml / m 2 , weigh after each sintering, the weight increase is 2.8-3.5g / m 2 After the last sintering, the total weight added by spraying on the titanium mesh substrate is 28-35g / m 2 .
[0099] Product testing indicators:
[0100] 1. Chlorine evolution potential test results: 1.10V-1.12V (indicators: current density 4KA / ㎡, saturated brine, temperature 90℃±1℃, ≤1.13VVS SCE);
[0101] 2. Strengthened weight loss test results: <5.5mg (index: 30% WtNaoH solution (CP grade), test piece 10C㎡, temperature 90℃±1℃, current density 20KA / ㎡, electrolysis 4 hours, weight loss <6.3mg);
[0102] 3. Tests in a small experimental electrolytic cell device showed that the electrolysis voltage was lower than that of the anode currently used; the purity of chlorine was greater than 98.6% (without acid addition process), and the oxygen content was less than 0.7%.
[0103] Embodiment 3:
[0104] Titanium mesh substrate: mesh pitch 4.5*8mm, thickness 1mm;
[0105] Anode coating coating liquid: solid ruthenium trichloride, chloroiridic acid, chloroplatinic acid, titanium tetrachloride, palladium chloride and n-butanol, with a formula composition of Ru40:Ir12:Pt9:Ti35:Pd4 in atomic percentage;
[0106] The final mass ratio of each raw material used is calculated as follows:
[0107] Ruthenium trichloride:iridium tetrachloride:chloroplatinic acid:titanium tetrachloride:palladium chloride=82.1:20.9:18.9:138.9:26.3.
[0108] Production of anode coating: 10 cycles of spraying, drying and sintering, with each spraying volume of 40-45ml / m 2 , weigh after each sintering, the weight increases by 3-3.5g / m 2After the last sintering, the total weight added by spraying on the titanium mesh substrate is 30-35g / m 2 .
[0109] Product testing indicators:
[0110] 1. Chlorine evolution potential test results: 1.10V-1.12V (indicators: current density 4KA / ㎡, saturated brine, temperature 90℃±1℃, ≤1.13VVS SCE);
[0111] 2. Strengthened weight loss test results: <5mg (index: 30% WtNaoH solution (CP grade), test piece 10C㎡, temperature 90℃±1℃, current density 20KA / ㎡, electrolysis 4 hours, weight loss <6.3mg);
[0112] 3. Tests in a small experimental electrolytic cell device showed that the electrolysis voltage was lower than that of the anode currently used; the purity of chlorine was greater than 98.8% (without acid addition process), and the oxygen content was less than 0.6%.
[0113] The above are only specific application examples of the present invention and do not constitute any limitation on the protection scope of the present invention. Any technical solution formed by equivalent transformation or equivalent replacement shall fall within the protection scope of the present invention.
Claims
1. An ion membrane electrolyzer, comprising a cell frame, on which a plurality of electrolytic cell groups (8) are arranged, characterized in that Both ends of the multiple electrolytic cell groups (8) are locked by copper bar end plates, respectively. The copper bar end plates are copper bar end plates fixed on a fixed seat or movable copper bar end plates fixed on a top rod seat. Different numbers of electrolytic cell groups (8) and copper bar end plates for locking the multiple electrolytic cell groups (8) are selected according to production capacity requirements. The copper bar end plates are connected to a power source. Each electrolytic unit cell group (8) is provided with a liquid inlet and a liquid outlet, respectively; the liquid inlet at the lower end of each electrolytic unit cell group (8) is connected to the same liquid inlet distribution pipe (10) via a liquid inlet pipe (9) at a corresponding position, and the liquid outlet at the upper end of each electrolytic unit cell group (8) is connected to the same liquid outlet main pipe (12) via a liquid outlet pipe (11) at a corresponding position; The liquid inlet pipe (9) and the liquid outlet pipe (11) are made of fluoroplastic flexible hoses; The electrolytic cell group (8) comprises an anode unit (801), a cathode unit (802) and an ion membrane (803) arranged therebetween; the frame bar of the anode unit (801) and the frame bar of the cathode unit (802) are connected via a screw group (804); an insulating gasket (805) is arranged between the frame bar of the anode unit (801) and the frame bar of the cathode unit (802); and sealing strips (806) are arranged between the insulating gasket (805) and the frame bars on both sides; The anode unit (801) comprises an anode disk (801.1), wherein a concave portion formed by bending the anode disk (801.1) forms an anode chamber, an anode gas-liquid separation box (801.2) is arranged at the upper end of the anode chamber, a vertically arranged anode rib plate (801.3) is arranged in the anode chamber below the anode gas-liquid separation box (801.2), a titanium-nickel composite plate (801.7) is arranged at a position corresponding to the anode rib plate (801.3) on the back of the anode disk (801.1), an anode mesh (801.4) is arranged on the top surface of the anode rib plate (801.3), obliquely arranged circulation plates (801.5) are arranged between adjacent anode rib plates (801.3), and an anode liquid inlet insertion tube (801.6) is arranged at the lower end of the anode chamber; The cathode unit (802) comprises a cathode disk (802.1), a cathode chamber is formed by a depression formed by bending the cathode disk (802.1), a cathode gas-liquid separation box (802.2) is arranged at the upper end of the cathode chamber, a cathode rib plate (802.3) arranged vertically is arranged in the cathode chamber below the cathode gas-liquid separation box (802.2), a cathode bottom net (802.4) is arranged on the top surface of the cathode rib plate (802.3), a cathode elastic net (802.5) is arranged on the surface of the cathode bottom net (802.4), a cathode surface net (802.6) is arranged on the surface of the cathode elastic net (802.5), and a cathode liquid inlet insertion tube (802.7) is arranged at the lower end of the cathode chamber; A sacrificial electrode for absorbing reverse current is also installed in the cathode chamber; The anode mesh adopts a titanium plate expanded mesh, and an active coating is arranged on the titanium plate expanded mesh, the active coating is an anode coating for an ion membrane electrolyzer, and the formula of the anode coating for the ion membrane electrolyzer is a combination formula of ruthenium, iridium, platinum, and titanium, wherein the ruthenium content is 35-45mol%, the iridium content is 5-15mol%, the platinum content is 5-10mol%, the titanium content is 35-45mol%, and other additives less than 4%mol%, the other additives are zirconium chloride or palladium chloride, wherein the carrier of ruthenium is ruthenium trichloride, the carrier of iridium is iridium tetrachloride or chloroiridic acid, the carrier of platinum is chloroplatinic acid or platinum chloride, and the carrier of titanium is titanium tetrachloride; The method of making the anodic coating is as follows: The raw materials are proportioned to form a coating liquid, and the various raw materials are as follows: a. ruthenium trichloride; b. titanium tetrachloride; c. iridium tetrachloride or chloroiridic acid; d. chloroplatinic acid or platinum chloride; e. zirconium chloride or palladium chloride can be used as an additive; f. a solvent selected from aqueous hydrochloric acid solution, ethylene glycol-butyl ether or n-butanol; Wherein ruthenium trichloride refers to a ruthenium trichloride hydrochloric acid aqueous solution containing 80-120 g / L of ruthenium or solid ruthenium trichloride with a content of 37%; titanium tetrachloride refers to a chemically pure titanium tetrachloride standard reagent; iridium tetrachloride refers to an iridium tetrachloride hydrochloric acid aqueous solution containing 80-120 g / L of iridium; Then the coating liquid is evenly coated on the titanium mesh substrate to finally form stable precious metal oxide crystals on the surface of the titanium mesh substrate; The specific steps of uniformly coating the coating liquid on the titanium mesh substrate to finally form stable precious metal oxide crystals on the surface of the titanium mesh substrate are as follows: The pre-treated titanium mesh substrate is subjected to multiple automatic electrostatic spraying, drying, and high-temperature sintering in an oxidation furnace according to the coating amount requirements. After the last sintering, the total spray weight increase on the titanium mesh substrate is 25-35g / m 2 , and finally carry out sintering and inspection, wherein the drying temperature is 80-90℃, the high temperature sintering temperature of the oxidation furnace is 400-500℃, the high temperature sintering time of the oxidation furnace is 0.5-1h, and the final sintering temperature is 480-530℃, the sintering operation is carried out slowly heating and cooling, and the sintering time is 8-12h; According to the total weight increase after sintering, 8-12 cycles of spraying, drying and sintering are carried out, and the spraying amount of each cycle is 40-60ml / m 2 , weigh after each sintering, the weight increases by 2-4g / m 2 .
Citation Information
Patent Citations
Electrode structure for electrochemical device
CN101265587A
Electrode for electrolysis, preparation method of electrode and electrolytic bath
CN104562078A
Bipolar zero-gap electrolytic cell
CN1717507A
Ionic membrane electrolytic cell
CN210736910U